Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
3(x+6)=2x-1
3x+18=2x-1
x= -19
-6(x-1)=2(x+8)
-6x+6=2x+8
-8x=2/:(-8)
x= -2/8= -1/4
(x+1)(x-2)=2x+x²
x²-2x+x-2=2x+x²
-x-2=2x
-3x=2/:(-3)
x= -2/3
-(x+1)(x-6)=-x²+9x
-(x²-6x+x-6)= -x²+9
-(x²-5x-6)= -x²+9
-x²+5x+6=x²+9
5x=3/:5
x=3/5
5(x+3)=1/9x-2
5x+15=1/9x -2
4 8/9x= -17
44/9x= -17 /*(9/44)
x= -153/44= -3 21/44
1/6x+2/3=7+x /*6
x+4=42+6x
-5x=38/:(-5)
x= -38/5= -7 3/5
x/8=x+9(x-1)
x/8=x+9x-8
x/8=10x-8 /*8
x=80x-64
-79x= -64/:(-79)
x=64/79
0,3+7(x-2)=5,3x
0,3+7x-14=5,3x
7x-13,7=5,3x
1,7x=13,7/:1,7
x=137/10 :17/10
x=137/10*10/17
x=137/17=8 1/17
7x+8=15
7x= 7/:7
x=1
6x-2=16
6x=18/:6
x=3
3x+9=x-1
2x= -10/:2
x=-5
1/7x=14 /*7
x=98
1/5x+2=7
1/5x=5/*5
x=25
16-4x=8+3x
-7x=-8 /:(-7)
x= 8/7=1 1/7
8x=30/:8
x=30/8=3 6/8=3 3/4
y:5=8 /*5
y=40
x-9=3x+1
-2x=10/:(-2)
x= -5